Cryochemically Obtained Nanoforms of Antimicrobial Drug Substance Dioxidine and Their Physico-chemical and Structural Properties - Tatyana I. Shabatina; Olga I. Vernaya; Vladimir P. Shabatin; Iuliia V. Evseeva; Michail Ya Melnikov; Andrew N. Fitch; Vladimir V. Chernyshev (Crystals, 2018)
Nanoforms of the antimicrobial drug substance 2,3-bis-(hydroxymethyl) quinoxaline-N,N′-dioxide with particles sizes between 50 and 300 nm were obtained by cryochemical modification of the initial pharmaceutical substance using a freeze-drying technique and were characterized by different physicochemical methods (FTIR, UV-Vis, 1H-NMR, DSC, TG and X-ray diffraction) and transmission electron microscopy (TEM). The data obtained from FTIR- and UV–Vis-spectroscopy confirmed the unaltered chemical structure of dioxidine molecules due to the cryochemical modification method. At the same time, X-ray diffraction and thermal analysis data show the change of the crystal structure compared to the parameters of the initial pharmaceutical dioxidine substance. A higher dissolution rate was revealed for cryomodified dioxidine nanoforms. The existence of three polymorphic crystal phases was established for cryomodified dioxidine samples possessed by some thermal activation processes: two anhydrous polymorphic phases, triclinic (T) and monoclinic (M), and one hydrated form (H).